Self-Orthogonal Codes From Row Orbit Matrices of Strongly Regular Graphs - Maksimović, Marija (Sarajevo Journal of Mathematics, 2020)
We show that under certain conditions submatrices of row orbit matrices of strongly regular graphs span self-orthogonal codes. In order to demonstrate this method of construction, we construct self-orthogonal ternary linear codes from orbit matrices of the strongly regular graphs with parameters (70,27,12,9). Also we construct non self-orthogonal binary linear codes from these orbit matrices. Further, we obtain strongly regular graphs and block designs from codewords of the constructed codes.